2021
DOI: 10.1186/s12937-021-00727-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Up to 82% critically ill patients had low Vitamin C values

Abstract: There are limited proven therapeutic options for the prevention and treatment of COVID-19. We underwent an observational study with the aim of measure plasma vitamin C levels in a population of critically ill COVID-19 adult patients who met ARDS criteria according to the Berlin definition. This epidemiological study brings to light that up to 82% had low Vitamin C values. Notwithstanding the limitation that this is a single-center study, it nevertheless shows an important issue. Given the potential role of vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…A brief research letter reported that vitamin C levels were undetectable in more than 90% of COVID-19 patients suffering with ARDS [67]. In addition, an epidemiological study reported that up to 82% of critically ill COVID-19 adult patients with ARDS had low vitamin C values [68]. This is consistent with low plasma levels of vitamin C reported in critically ill patients and many other conditions.…”
Section: Vitamin C Lessens Alveolar Damage and Lung Complicationssupporting
confidence: 56%
“…A brief research letter reported that vitamin C levels were undetectable in more than 90% of COVID-19 patients suffering with ARDS [67]. In addition, an epidemiological study reported that up to 82% of critically ill COVID-19 adult patients with ARDS had low vitamin C values [68]. This is consistent with low plasma levels of vitamin C reported in critically ill patients and many other conditions.…”
Section: Vitamin C Lessens Alveolar Damage and Lung Complicationssupporting
confidence: 56%
“…The vitamin C status of patients with COVID-19 has been reported in several small observational studies (Table 1) [21][22][23][24][25][26]. Plasma concentrations of vitamin C in most of these patients were reported to be very low with 70-80% of the patients having hypovitaminosis C (plasma concentration <23 µmol/L) [22,24]. The low concentrations were despite patients receiving on average 124 mg/day vitamin C in their enteral or parenteral nutrition [26].…”
Section: Vitamin C Status In Patients With Covid-19mentioning
confidence: 94%
“…Significant evidence indicates that patients with severe respiratory infections have depleted vitamin C status, with the prevalence of deficiency increasing with the severity of the condition [18][19][20]. The vitamin C status of patients with COVID-19 has been reported in several small observational studies (Table 1) [21][22][23][24][25][26]. Plasma concentrations of vitamin C in most of these patients were reported to be very low with 70-80% of the patients having hypovitaminosis C (plasma concentration <23 µmol/L) [22,24].…”
Section: Vitamin C Status In Patients With Covid-19mentioning
confidence: 99%
“…The hypothesis regarding the benefits related to VC administration in severe cases of infection is based on the observation that, in this group of patients, levels of ascorbic acid during the recovery period are very low and, in many cases, undetectable [ 180 , 181 ]. In healthy people, ascorbic acid serum levels are about 0.4–2.0 mg/dL [ 180 ]. There is evidence that the majority of critically ill COVID-19 patients has low-to-undetectable VC levels.…”
Section: Vitamin Cmentioning
confidence: 99%
“…There is evidence that the majority of critically ill COVID-19 patients has low-to-undetectable VC levels. Tomasa-Irriguible and Bielsa-Berrocal [ 180 ] found that, in 82% of patients, within 24 h of ICU admission, the VC was below the normal range, with a mean value of 0.14 mg/dL (+/− SD 0.05 mg/dL). Similar results were observed by Chiscano-Camón et al [ 181 ]—undetectable ascorbic acid levels were found in 94.4% of ICU patients with SARS-CoV-2-associated ARDS.…”
Section: Vitamin Cmentioning
confidence: 99%